The Role of Strategic Management in Developing the Financial Efficiency of the banking sector: an applied study in a number of Iraqi private banks - حاضر, صباح شعير (Finance and Business Economies Review, 2019)
The study aimed at revealing the role of strategic management in developing the financial efficiency of the private banking sector. A questionnaire was distributed to 100 employees (branch manager, operations manager, customer services officer, special services officer, chief cashier) (The Bank of Ashur International - Bank of Baghdad - Gulf Commercial Bank). The results of the study showed that the reality of applying the strategic management method in the private banking sector in Iraq was good from the point of view of the study sample. The results also showed that applying the strategic management method in the private banking sector affects the development of the financial efficiency of these banks.